You belong to me - Lindsey, Johanna; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1994)
In the sequel to the best-selling Once a Princess, the beautiful, liberal-minded Alexandra Rubliov and the handsome, rakish Count Vasili Petroff are determined to resist the betrothal arranged for them by Alexandra's father, but cannot curb their passion.
Keywords: Love stories; Historical fiction